Education on the utilization of butterfly pea flower (Clitoria ternatea) as a natural dye for students of SDN Tlogosari Wetan 2 Semarang - Kusumawati, Dwi Endah; Rizki, Inesya Febrianing; Lestari, Asih Puji; Nabilla, Nabilla; Nurningtyas, Hasna Labibah; Chaqi, Muhammad Dhiya'ul; Prasetyo, Adhi (Universitas Muhammadiyah Magelang, 2025)
Butterfly pea flower is rich in anthocyanins, which not only provide a natural blue color but also offer health benefits. The purpose of this community service is to educate students about the benefits of butterfly pea flower as a natural dye. The activity began with an introduction to butterfly pea flower and anthocyanins, followed by practical application of using butterfly pea flower as a natural dye in making pudding. This activity successfully increased students' knowledge about the use of natural dyes from butterfly pea flower by 100%. When applied to pudding, butterfly pea flower, which contains anthocyanins, proved to be usable as a natural dye. In addition, this activity also educated students about the diversity of local food ingredients that can be optimally utilized.